INTEGRATING QUR'ANIC ETHICS WITH SDGS: A THEMATIC STUDY OF SURAH AL-BAQARAH VERSES 30 AND 275-279 - Nurma Sari; Akmal Tarigan; Rahmi Syahriza; Cut Fauziah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
The Qur'an as a guide to life for Muslims offers universal guidance that covers various aspects of life, including economic development and social sustainability. Surah Al-Baqarah verse 30 and verses 275-279 are ethical theological foundations in building governance that is fair, sustainable, and free from economic injustice. The Qur'anic approach to human development is not only normative but also provides practical solutions. The prohibition of usury, the recommendation of zakat, infaq, sadaqah, and human responsibility as khalifah are integral mechanisms to create inclusive and sustainable development. Therefore, this study aims to examine the relationship between the values contained in Surah Al-Baqarah verses 30 and 275-279 with the goals of SDGs by using a thematic interpretation approach. The results show that achieving the SDGs requires the integration of spiritual values, as taught in the Qur'an, to complement technical and economic approaches. Therefore, the Qur'an can be the main reference in addressing various global issues through a holistic approach that incorporates ethics.